Intracoronal radiolucencies in unerupted teeth of orthodontic patients: three case reports - Jacobs Stanley G. (Sciendo, 1991)
Three cases of intracoronal radiolucencies in unerupted teeth are reported. The aetiology and treatment of this condition which may first be detected by the orthodontist are discussed. In extreme cases, involved teeth may be lost.